The Mechanisms of Chansu in Inducing Efficient Apoptosis in Colon Cancer Cells. (30th May 2013) - Li, Chun; Hashimi, Saeed M.; Cao, Siyu; Mellick, Albert S.; Duan, Wei; Good, David; Wei, Ming Q.
Abstract : Chansu is one of the most widely used traditional Chinese medicines in China, Japan, and other Southeast Asian countries primarily for antipain, anti-inflammation, and recently anticancer. Over 10 recipes and remedies contained Chansu, which are easily available in pharmacies and hospitals, but the mechanisms of action were not clearly articulated. In the present study, Cinobufagin (CBF), the major compound of Chansu, was employed as a surrogate marker to determine its ability in inducing cancer cell death. As expected, CBF has significant cancer-killing capacity for a range of cancers, but such ability differs markedly. Colon and prostate cancers are more sensitive than skin and lung cancers. Interestingly, cancer cells die through apoptotic pathway either being biphasic caspase-3-dependent (HCT116) or independent (HT29). Multipathway analysis reveals that CBF-induced apoptosis is likely modulated by the hypoxia-inducing factor-1 alpha subunit (HIF-1 α ) as its inhibition was evident in vitro and in vivo . Taken together, these results demonstrate that CBF is a potent apoptotic inducer with potential for further development as a novel and effective anticancer agent for a range of cancers, especially colon cancer.